Uncertainty in cyber de-responsibilisation. Issue 8 (August 2021) - Renaud, Karen; Flowerday, Stephen; van der Schyff, Karl
Abstract : The sociologist Norbert Elias argued that the ability to take responsibility is part of a 'civilizing process'. 1 Neoliberal governments appear to agree with this, because they have 'responsibilised' their citizens in many domains. 2 Pellandini-Simányi and Conte explain that the concept of responsibilisation refers to the assigning of responsibility to citizens and the social-cultural factors that persuade citizens to embrace those responsibilities. 3